Correction: Estimation of Dietary Iron Bioavailability from Food Iron Intake and Iron Status. - Jack R Dainty; Rachel Berry; Sean R Lynch; Linda J Harvey; Susan J Fairweather-Tait (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0111824.].